Pemenuhan Kebutuhan Hierarki Abraham Maslow dalam Dinamika Keluarga: Analisis Film “Keluarga Cemara2” - Reski Reski; Irma Satriani (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This article presents an analysis of the fulfillment of Abraham Maslow's hierarchical needs in the family dynamics shown in the film